Differences in Ethical Judgment between Accounting Students: An Experiment using Ethical-dilemma Movie and Ignatian Pedagogical Paradigm - Antonious Diksa Kuntara (Sebelas Maret Business Review, 2018)
The study tries to seek evidence whether the ethical judgment of the accounting students following treatment of watching ethical-dilemma movie and make a reflection as suggested by Ignatian Pedagogical Paradigm Approach. The study is a quasi-experimental using posttest only with an experimental and control group approach. Using the respondents of senior accounting students in a university in Indonesia, we found no ethical judgment difference between students received the treatment and the control group. However, the score of the treated group was higher than the score of the control group. Under a specific limitation, this study suggests that a reflective learning method is an excellent idea to improve students' ethical judgment.